Combination of Paeoniae Radix and Cnidii Rhizoma Prolonged Survival of Fully Mismatched Cardiac Allografts and Generated Regulatory Cells in Mice - Jin, Xiangyuan (Hindawi Publishing Corporation, 2014)
In previous studies, we have demonstrated that Tokishakuyakusan (TJ-23) can prolong the survival of allogeneic cardiac grafts and induce regulatory T cells. In this study we investigated the effects of Paeoniae radix and Cnidii rhizoma, two components of TJ-23, on alloimmune responses in a murine cardiac transplantation model and whether the two agents have synergistic effect. CBA mice underwent transplantation of a C57BL/6 heart and received oral administration of 2 g/kg/day of Paeoniae radix, Cnidii rhizoma, or the mixture of two agents from the day of transplantation until 7 days afterward. Naïve CBA mice rejected C57BL/6 cardiac graft acutely (median survival time (MST): 7 days). Paeoniae radix and Cnidii rhizoma prolonged C57BL/6 allograft survival (MSTs: 13.5 and 15.5 days, resp.). However, the mixture of two agents prolonged C57BL/6 allograft survival indefinitely (MST > 100 days). Secondary CBA recipients given whole splenocytes from primary combination-treated CBA recipients with B6 cardiac allografts 30 days after grafting had prolonged survival of B6 hearts (MST: 33 days). Flow cytometry studies showed that the CD4(+)CD25(+)Foxp3(+) regulatory cell population was increased in combination-treated recipients. Combination of Paeoniae radix and Cnidii rhizoma induced hyporesponsiveness to fully allogeneic cardiac allografts and may generate CD4(+)CD25(+)Foxp3(+) regulatory cells in our model.